Vida, encaixes e sonhos: um olhar sobre a produção artística de Luís Karimal - Maria Eneida Feitosa (2017)
This thesis brings reflections on some aspects of the imagery potentiality of this artist's work. The fundamental assumption is the idea of bringing to the academic universe a critical discussion about this know-how and to enable a discursive transversality. As suggested by the title, this work is distributed into three parts. The first one presents the artist through his reports, shows a survey of his history portrayed in interviews and newspaper reports and chronologically discuss his trajectory, as well as presents a survey of his production. The second part establishes a thematic division and analyzes some of his works in which there is the technique of narrative fittings, which is a way to attribute meanings. This second part is subdivided into the place where this artistic manifestation took place and the production directed towards the feminine. In the first parte we present possibilities of understanding this knowledge, which took place in Cariri Cearense, and we show the imagery worldview of this locus. In the second part, we discuss one of the most popular subjects in the adult phase of Karimai´s production, the feminine; to observe dialogues and metaphorical relations between the narratives embedded in the canvas guides our search. Finally, we present a freer observation that allows us to point out constitutive and recurrent elements of this production as a fundamental constructive element of this manifestation in the creative process for which Luís Karimai makes use of his own symbology. To discuss such aspects is the support of this thesis that reflects and invites to the look of an artistic-pictorial projection that thematizes human existence.